You've reached sam eaudiobook A novel. - Thao, Dustin (Macmillan Young Listeners, 2021)
An Instant New York Times Bestseller! If I Stay meets Your Name in Dustin Thao's You've Reached Sam , a heartfelt audiobook about love and loss and what it means to say goodbye. Seventeen-year-old Julie Clarke has her future all planned out—move out of her small town with her boyfriend Sam, attend college in the city; spend a summer in Japan. But then Sam dies. And everything changes. Heartbroken, Julie skips his funeral, throws out his belongings, and tries everything to forget him. But a message Sam left behind in her yearbook forces memories to return. Desperate to hear him one more time, Julie calls Sam's cell phone just to listen to his voice mail recording. And Sam picks up the phone. The connection is temporary. But hearing Sam's voice makes Julie fall for him all over again and with each call, it becomes harder to let him go. What would you do if you had a second chance at goodbye? A Macmillan Audio production from Wednesday Books